Test of Blade Number of Irrigation Water Power Plant Equipment - Amanda Buna Satria Siregar; Saipul Bahri Daulay; Sulastri Panggabean (Universitas Sumatera Utara, 2016)
In Power plant Irrigation water ,one of the component of the turbines is the blade. This study was aimed to examine the number of blades on water mill power generation in Medan Krio Irrigation. This study used a non-factorial completely randomized design (CRD) with 8, 10, and 12 blades respectively. Parameters observed were flow rate power, voltage, rpm generator rotation. The result showed that the mean flow rate were 0,040 m blade /s at the 8 blades; 0,047 /s at the 10 blade and 0,048 /s at the 12 blade. The mean electric power was 161.180 Watt at the 8 blades; 175.120 Watt at the 10 blade; and 181.380 Watt at the 12 blade . Electric voltage mean was 7.418 volts at the 8 blade; 7.582 volts at the 10 blade of; 8.242 volts and at the 12 blade. Mean of the water miil rpm was at the 64.618 rpm at the 8 blade; was 66.190 rpm at the 10 blade; was 67.480 rpm at the 12 blade. The mean generator Rpm 1332.744 rpm at the blade; 1369.605 rpm at the 10 blade and 1391.781 rpm at the 12 blade Keywords: water mill, Irrigation, Blade, Electrical Power